Real Exchange Rate and Trade Balance Dynamics in Cote d’Ivoire - Keho, Yaya (International Journal of Economics and Financial Issues, 2021)
This study examines the relationship between real exchange rate and trade balance in Cote d’Ivoire during the period from 1975 to 2017. The study employs the ARDL bounds testing approach to cointegration developed by Pesaran et al. (2001) in the examination of this nexus. Cointegration analysis and error correction modeling are used to determine the long run as well as short run dynamics, between real exchange rate and trade balance. The empirical results show negative and significant effects of domestic income on trade balance both in the short and long run. Further, a depreciation of real exchange rate causes an improvement in the trade balance in a significant way both in the short and long run. This suggests that exchange rate variations are effective for increasing balance of trade for Cote d’Ivoire. Keywords: trade balance, real exchange rate, bounds test, Cote d’Ivoire JEL Classifications: C22, F10, F31 DOI: https://doi.org/10.32479/ijefi.10857